Curso de formação para docência online: uma proposta para a formação continuada - Costa, Natália Xavier Pereira da (2019)
The present research sought to elaborate a Training Course in Teaching Online, product presented here in the format of an Activity Map, an Instructional Design resource. Although it is based on the physical distance between the teacher and students, Distance Education replaces bidirectional logic with multidirectional and requires the rapid adaptation of students and teachers to the use of new technologies that are increasingly incorporated into this modality. In this scenario, it becomes necessary, more and more, a professional capable of mediating between the student and the knowledge in a differentiated and effective way: the online teacher. Using the methodological approach of action research (CARR; KEMMIS, 1986), sixteen professors from UNIGRANRIO University showed elements that could contribute to the construction of the product as a form of intervention for the improvement of work in EAD. For the analysis of the data collected during this research and for the elaboration of the educational product proposed here we used the Content Analysis from Bardin's perspective. Three meetings were held with the online teachers in order to discuss and present proposals for the problem of continuing education necessary to make the teacher of the tutor. Through the product developed here it is possible to visualize the construction of knowledge and all the paths that must be crossed by the online teacher, so that this professional can mediate, monitor and evaluate the learning autonomously. From authors such as Filatro (2008), Santos (2012), Silva (2009), Tardif (2010) and Vigotsky (1991), it was hypothesized that there are specific demands for the teacher's performance in the distance modality, creation of continuing education courses for online teachers has proved to be a relevant strategy to facilitate the understanding of the work performed by this professional.